The acquisition of Setswana phonology in children aged 2;0 – 6;5 years - Mahura, Olebeng (Department of Anaesthesia and Perioperative Medicine, 2022)
This study aimed to describe the phonological development of Setswana-speaking children between the ages of 2;0 and 6;5 years. The study objectives were to: 1) describe the acquisition of four aspects of phonology in these children, namely vowels, consonants, lexical tone and phonological processes; 2) contrast Setswana phonological development in monolingual vs multilingual children; and 3) contrast typical vs atypical Setswana speech acquisition and determine the occurrence and nature of speech sound disorders in children acquiring Setswana. The participant group comprised 81 children from the North-West Province of South Africa. All children were attending preschool and were acquiring one of two varieties of Setswana investigated in this study, namely Sekwêna and Setlhaping. Sixty-five participants were acquiring Sekwêna and were recruited from Hebron, and the remaining 16 participants were acquiring Setlhaping and were recruited from Dry-Harts village. The study used a cross-sectional design to detail the stages of phonological development in children aged 2;0–6;5 years. For each of the varieties studied, participants were assigned to groups of six-month age bands (e.g. 2;6– 2;11 years). Findings add to data from a preliminary pilot study on the acquisition of Setswana segmental phonology (Mahura, 2014; Mahura & Pascoe, 2020). Prior to obtaining speech samples from Setswanaspeaking children, revisions were made to the assessment developed in the pilot study. This was done by addressing a number of limitations which had been documented following its use, including ensuring that all consonant phonemes were targeted in the initial word and penultimate syllable positions, as well as including syllabic consonants in these word positions. The picture stimuli were also changed, and an expert panel assessed the revised word list to ensure that all words were linguistically and culturally appropriate. Participants' speech was transcribed online using IPA symbols and audio recorded for later re-transcription to ensure reliability. The findings indicate that children acquiring Setswana have a full set of vowels in their phonetic inventories as early as 2;6 years, and possibly earlier. A large number of consonant phonemes occurring in the Setswana phonological system had either been acquired or mastered by 2;6–2;11 years. This was seen word-initially and in the penultimate syllable position, with only three phonemes still to be acquired at this age word-initially: only two phonemes with rounding, velar plosive /kʷʼ/ and alveolar nasal /nʷ/, were still emerging at 2;6–2;11 years and seen to be acquired at 3;0–3;5 years in the initial word position and voiced palato-alveolar affricate /ʤ/ was absent at 2;6–2;11 years. This phoneme was, however, seen to emerge in the 3;0–3;5-year group. Heterorganic compounds in the initial word position mainly consisted of /fj/ and were only seen in the speech of children who speak the Sekwêna variety. Conclusions on the age at which heterorganic compound /fj/ is acquired could not be made as it was not used by all children acquiring the Sekwêna variety, but instead observed in the speech of several participants across the different age bands. Although consonant clusters were not included in the consonant phonemes elicited as part of this study, they were noted in the inventories of children across the different age groups. A clear reduction in the occurrence of phonological processes was seen across age group, a pattern of development that can be expected in typically-developing children. Some of the phonological processes seen in Setswana-speaking children included assimilation (eliminated after 6;5 years), fronting (eliminated at 3;6 yeas), and stopping (eliminated at 4;0 years). Correct use of lexical tone was observed as early as 2;6–2;11 years. Furthermore, the speech sound skills of bi/multilingual children were found to be comparable to their monolingual peers, and sometimes slightly more advanced. Findings are related to existing theoretical frameworks used to describe speech sound acquisition. While the findings from this study are not yet generalisable to all Setswana-speaking children, they indicate that theoretical frameworks such as Stackhouse and Wells' (1997) psycholinguistic approach and Dodd's (1995; 2005) diagnostic framework can be applied to Setswana. Language specific differences that should be taken into account are presented. This data adds to knowledge on speech sound acquisition in Setswana-speaking children, urgently needed for the early assessment and identification of children with speech difficulties, which has been lacking to date. When speech difficulties are identified and addressed early, children's academic, psychosocial and life outcomes can be improved, but Setswana-speaking children are often not well served by speech and language therapists in South Africa due to a lack of relevant information and resources. This study set out to redress this situation. Lines for future research include using a larger sample of participants to allow data to be more generalisable, developing assessments for speech input processing as well as production and considering aspects of tone more comprehensively.